Recepcja literackiej Nagrody Nobla dla Elfriede Jelinek w wybranych dziennikach i tygodnikach polskich z 2004 roku. Przyczynek do analizy zjawiska = The Nobel Prize in Literature for Elfriede Jelinek reception in chosen Polish daily newspapers and weekly magazines from 2004. Contribution to an analysis of the phenomenon - Rawski, Jakub (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article is an attempt to analyse reception of The Nobel Prize in Literature for ElfriedeJelinek in the Polish press (dailies and weeklies) in 2004. The study was carried out in order to answer the following questions: how were the Nobel Prize winner and her work presented? Did ideological variety of newspapers influence on the assessment of the verdict set by the Academy? Did Elfriede Jelinek's political involvement affect the evaluation of her output? A
Keywords: Jelinek, Elfriede (1946 -); Nagroda Nobla; recepcja; prasa polska; The Nobel Prize in Literature; reception; the Polish press